2015
DOI: 10.1186/s12879-015-0753-y
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of antiretroviral adherence among HIV positive children and teenagers in rural Tanzania: a mixed methods study

Abstract: BackgroundAround 3.3 million children worldwide are infected with HIV and 90% of them live in sub-Saharan Africa. Our study aimed to estimate adherence levels and find the determinants, facilitators and barriers of ART adherence among children and teenagers in rural Tanzania.MethodsWe applied a sequential explanatory mixed method design targeting children and teenagers aged 2–19 years residing in Ifakara. We conducted a quantitative cross sectional study followed by a qualitative study combining focus group di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
110
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(123 citation statements)
references
References 39 publications
11
110
2
Order By: Relevance
“…The use of treatment reminders was associated with better adherence while the use of PI-based regimens predicted poorer adherence. The adherence rate in the current study is better than those reported from several low, middle and high income countries (Bhattacharya & Dubey, 2011;Kim, Gerver, Fidler, & Ward, 2014;Nyogea et al, 2015;Reda & Biadgilign, 2012;Ugwu & Eneh, 2013). …”
Section: Discussioncontrasting
confidence: 52%
“…The use of treatment reminders was associated with better adherence while the use of PI-based regimens predicted poorer adherence. The adherence rate in the current study is better than those reported from several low, middle and high income countries (Bhattacharya & Dubey, 2011;Kim, Gerver, Fidler, & Ward, 2014;Nyogea et al, 2015;Reda & Biadgilign, 2012;Ugwu & Eneh, 2013). …”
Section: Discussioncontrasting
confidence: 52%
“…Anticipated stigma (fears surrounding social exclusion) was common at the individual level, negatively influencing motivations to obtain an HIV diagnosis [39][40][41][42][43][44][45][46] and to follow up on test results [44,45]. This was reinforced by experiences with external stigma at other levels including: family neglect or ostracism from peers [39,40,43,[47][48][49][50], community gossip [41][42][43]46], discrimination in school [49,[51][52][53][54] or lack of empathy from health care workers (HCW) [45,50,[55][56][57]. Such social conditions reinforced barriers to HIV care linkage, retention in HIV services and adherence; with ALHIV often choosing to prioritize secrecy around their disease status over unintended disclosure [48,[51][52][53][54][55][57][58][59][60].…”
Section: Stigmamentioning
confidence: 99%
“…This was reinforced by experiences with external stigma at other levels including: family neglect or ostracism from peers [39,40,43,[47][48][49][50], community gossip [41][42][43]46], discrimination in school [49,[51][52][53][54] or lack of empathy from health care workers (HCW) [45,50,[55][56][57]. Such social conditions reinforced barriers to HIV care linkage, retention in HIV services and adherence; with ALHIV often choosing to prioritize secrecy around their disease status over unintended disclosure [48,[51][52][53][54][55][57][58][59][60]. This choice frequently accounted for missed ART doses when social conditions were unfavourable, such as having minimal privacy in the home [49,51,53,57] or at school [49,52].…”
Section: Stigmamentioning
confidence: 99%
See 1 more Smart Citation
“…Among these factors, some of them are unfavorable school environment, pills burden of the HIV drug, treatment longevity, being unaware of HIV status, non-parental care, preference for traditional medicine and forgetfulness [3538]. …”
Section: Introductionmentioning
confidence: 99%